Numerical solution for one dimensional thermal problems using the finite element method / Hisham Md. Basir - Md. Basir, Hisham (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2002)
Finite Element is a useful and effective numerical method for developing mathematical models to simulate problems related to stress analysis, heat transfer, electromagnetism and fluid flow. It uses a complex system of points, called nodes, which form a grid, or mesh, across the studied model. Every node assigned with an equation determines how the parameter will react to a certain load conditions. This paper discusses the formulation of that equation and the related solution based on the Galerkin's Weighted Residual Method.